MEDAN MAKNA PERALATAN RUMAH TANGGA DALAM BAHASA TALANG MAMAK DIALEK LANGKAH LAMA DI RIAU - Elvina Syahrir (Balai Bahasa Provinsi Riau, 2015)
This research discusses about the meaning components of household appliances in bahasa Talang Mamak Dialek Langkah Lama (BTMDLL), based on semantic field theory. The aim of this study is to describe about the meaning components of the household appliance lexemes in BTMDLL and its semantic functions. A descriptive method was used in order to get the data from the field research by recording, interview and writing. The results show that the meaning components of the BTMDLL household appliance lexemes can be known from the special meaning of each lexeme. The meaning components of each household appliance lexeme of BTMDLL has its own semantic function.